Analisis Wacana Pada Fenomena Pengunaan Artificial Intelligence (Ai) Dalam Konten Pemilu: Studi Kasus Konten Deepfake Soeharto Mengajak Untuk Memilih Partai Golkar Pada Media Sosial Twitter (X) - Santiko, Jetrin Arfan; Bahri, Syaiful (Innovative: Journal Of Social Science Research, 2024)
This research investigates the use of deepfake technology in political campaign content, particularly an AI-generated video depicting Soeharto urging the selection of the Golkar Party. The analysis is conducted through Norman Fairclough's discourse analysis framework, focusing on the descriptive aspect of the video content, production, distribution, and consumption of content, as well as its implications on socio-cultural practices. The findings reveal innovative strategies in political campaigning that leverage advancements in AI technology, albeit accompanied by ethical concerns regarding the use of an individual's image without consent. Responses from the audience depict a wide spectrum of reactions, from admiration for the technology to concerns about ethical implications and its impact on the integrity of political information. This study highlights new dynamics in political communication influenced by AI technology, underscoring the need to consider ethical, regulatory, and social impact aspects of technology use in a political context.